2013
DOI: 10.2147/ijwh.s45405
|View full text |Cite
|
Sign up to set email alerts
|

Pathways of cervical cancer screening among Chinese women

Abstract: BackgroundThe purpose of this community-based study was to develop a structural equation model for factors contributing to cervical cancer screening among Chinese American women.MethodsA cross-sectional design included a sample of 573 Chinese American women aged 18 years and older. The initial step involved use of confirmatory factor analysis, that included the following variables: access to and satisfaction with health care, and enabling and predisposing cultural and health beliefs. Structural equation model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
18
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 36 publications
5
18
2
2
Order By: Relevance
“…These results are supported by several other studies in Africa and elsewhere [11, 28, 29]. Higher SES is related to education, employment status and residence, all of which were found to be associated with screening in our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are supported by several other studies in Africa and elsewhere [11, 28, 29]. Higher SES is related to education, employment status and residence, all of which were found to be associated with screening in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Women’s employment relationship to screening status was demonstrated in a Chinese American study as well [29]. Income level and cost of screening, which is related to a patient’s or a patient’s family’s employment, was found to be an important factor in other studies investigating cervical cancer screening barriers.…”
Section: Discussionmentioning
confidence: 94%
“…Acquisition of HPV infection is strongly associated with sexual behavior. The prevalence of HPV increases with number of sexual partners and earlier sexual debut 3. Antibodies to HPV were detected more often in women who had had their first child at age older than 30 years.…”
Section: Discussionmentioning
confidence: 99%
“…Another reason could be the high sensitivity of the enzyme-linked immunosorbent assay that permits detection of the HPV antibody in samples with low HPV antibody which would probably otherwise have been scored as negative for HPV. It has been shown that detection of antibodies to HPV can evaluate the overall HPV infection rate in a population more effectively than HPV DNA 3. In view of this, and because Ahmadu Bello University Teaching Hospital is a referral center where patients from Zaria and its environs are seen, and 40% of the women attending the clinic there have been infected with HPV, this percentage represents the actual seroprevalence of HPV in the state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation